(untitled) (Texas Journal of Multidisciplinary Studies, 2025)
The article presents the results of field experiments conducted in 2025 in the Syrdarya region, aimed at evaluating the biological efficiency of the microbiological preparation CropGuard (IPL Biologicals Limited, India), containing entomopathogenic fungi Beauveria bassiana and Verticillium lecanii, against thrips (Thripidae) on cotton. As a reference standard, the biopreparation BioSleep BW based on the entomopathogenic fungus Beauveria bassiana (strain OPB-43) was used. The experiments accounted for the abundance of two thrips species: onion thrips (Thrips tabaci Lind.) and wheat thrips (Thrips angusticeps Uzel). The results showed that at an application rate of 3.0 L/ha, CropGuard reduced thrips density by 87.4%, which is comparable to the reference (84.1%). At a rate of 2.5 L/ha, the efficiency was 82.6%. No phytotoxicity or negative effects on beneficial entomophages were observed